Genetic mechanisms of sinter deposit zones in the Yangyi geothermal field, Tibet: Evidence from the hydrochemistry of geothermal fluid. (July 2022) - Wang, Xiao; Wang, Guiling; Gan, Haonan; Liu, Ning; Nan, Dawa; Liu, Zhao
Highlights: CO2 degassing took place during deep geothermal fluid ascent to the surface in Qialagai only. Equilibrium temperatures and water-rock interactions in the geothermal reservoirs are similar below the Bujimu and Qialagai valleys. Mixing ratio of cold groundwater in the up-flow zone of Bujiemu is 58–66% calculated by Cl − concentrations. Deep geothermal fluid reacts with shallow wallrock and does not reach water-rock re-equilibrium in the up-flow zone of Bujiemu. Genetic mechanisms of siliceous and calcareous sinters are clarified. Abstract: Yangyi is a typical high temperature geothermal field in the Tibetan Plateau. Massive siliceous and calcareous sinters have developed in the northern Qialagai Valley and the southern Bujiemu Valley, respectively. This suggests that the deep geothermal fluids in the northern and southern areas may experience different hydrogeochemical processes during ascent to the surface. By combining the analysis of hydrochemical composition, classical chemical geothermometers and multicomponent geothermometry with water-rock interaction models, this study analyzes the genetic mechanisms of the different types of sinters developed in the southern and northern parts of the same geothermal field. The equilibrium temperatures and degrees of water-rock interaction in the deep reservoirs are similar in the Bujimu and Qialagai valleys. CO2 degassing took place during deep geothermal fluid ascent to the surface in Qialagai only. This process leads to calcite precipitation, thus, Ca and HCO3 are consumed, leading to a deficiency in the formation of calcareous sinters. Deep geothermal fluids supersaturated with respect to SiO2 have cooled and precipitated rapidly as siliceous sinters in low-temperature and low-pressure environments. The deep geothermal fluids in Bujiemu mix with cold groundwater during ascent, and the mixing ratio of the cold groundwater is 58–66%, as calculated using Cl − concentrations. In the case of Bujiemu hot springs, the water-rock interaction models built with the PHREEQC program shows that calcite and fluorite dissolve along the flow path, which leads to an increase in the concentrations of Ca, HCO3, and F. The SiO2 concentration of the deep geothermal fluid is diluted by mixing with cold water, which leads to a deficiency of material for the formation of siliceous sinters. However, Ca and HCO3 concentrations are not significantly influenced, and the decrease in water temperature and dissolution of calcite and fluorite provides an advantage for the formation of calcareous sinters in the Bujiemu Valley.